Pengaruh Faktor Sosial Ekonomi Terhadap Perkembangan Indeks Pembangunan Manusia di Provinsi Papua Tengah Tahun 2018-2024 - Nilawati, Arum; Haqi, Alma Ainul; Riefky, Muhammad (Politeknik Statistika STIS, 2025)
Central Papua Province is the region with the second lowest human development index in Indonesia. The low human development index in Central Papua is due to socio-economic factors. This study aims to examine socioeconomic factors on the Central Papuan human development index in 2018–2024 with panel data regression. The data obtained from the secondary data of the official publication of the BPS of Central Papua Province in 2018-2024 with the variables used including the human development index, poverty rate, open unemployment rate, per capita expenditure, and life expectancy. The results of the analysis explained that the poverty rate, open unemployment rate, and per capita expenditure affect the human development index, while the life expectancy rate has no impact on the human development index. So that the results of this research can be used as a guideline for human development policies in Central Papua.